Transverse Colon Volvulus with Bowel Obstruction Management: A Case Report - Mubarah, Alanoud; Alanazi, Majed; Aljabali, Mohammed; Ali, Bandar (International Journal of Innovative Research in Medical Science, 2023)
Background: Very few cases of transverse colon volvulus have been reported in the literature. The condition is considered an emergency and needs urgent recognition and management before the affected patient develops peritonitis or bowel infarction. Case presentation: We report a case of a 70-year-old man with quadriplegia who experienced abdominal pain and constipation for 2 days. Abdominal radiography showed distended colon, and computed tomography (CT) revealed closed-loop obstruction with signs of bowel ischemia. Conclusion: Surgeons may not encounter such a case of transverse colon volvulus throughout their entire surgical career and early recognition is the cornerstone to a successful result.